Neonauclea reticulata (Havil.) Merr Stimulates Skin Regeneration after UVB Exposure via ROS Scavenging and Modulation of the MAPK/MMPs/Collagen Pathway. (15th June 2013) - Chiang, Hsiu-Mei; Chen, Hsin-Chun; Chiu, Hua-Hsien; Chen, Chien-Wen; Wang, Ssu-Meng; Wen, Kuo-Ching
Abstract : In this study, we investigated whether the protective effects of Neonauclea reticulata water extract against ultraviolet B (UVB) irradiation in human skin fibroblast cell cultures (Hs68) are governed by its ability to protect against oxidative stress and expression of matrix metalloproteinases (MMPs). We found that Neonauclea reticulata extract exhibited DPPH scavenging activity and inhibited AAPH-induced haemolysis of erythrocytes in a dose- and time-dependent manner. We also found that pretreatment of fibroblasts with Neonauclea reticulata water extract resulted in markedly lower levels of MMP-1, -3, and -9 expressions. Furthermore, our results indicate that Neonauclea reticulata extract inhibits the expression of MMPs by inhibiting ERK, JNK, and p38 phosphorylation. Our results also demonstrate that treatment with Neonauclea reticulata extract protects against UVB-induced depletion of collagen. In addition, Neonauclea reticulata extract did not have a cytotoxic effect. These findings indicate that the antioxidant activity of Neonauclea reticulata extract resulted in inhibition of MMP-1, -3, and -9 expressions and in increased levels of collagen activity. Our results suggest that Neonauclea reticulata extract can protect against photoaging.